Antithrombotic treatment in elderly patients with atrial fibrillation: a practical approach. Issue 1 (December 2015) - Suárez Fernández, Carmen; Formiga, Francesc; Camafort, Miguel; Cepeda Rodrigo, Jose María; Díez-Manglano, Jesús; Pose Reino, Antonio; Tiberio, Gregorio; Mostaza, Jose
Abstract Background Atrial fibrillation (AF) in the elderly is a complex condition. It has a direct impact on the underuse of antithrombotic therapy reported in this population. Discussion All patients aged ≥75 years with AF have an individual yearly risk of stroke >4 %. However, the risk of hemorrhage is also increased. Moreover, in this population it is common the presence of other comorbidities, cognitive disorders, risk of falls and polymedication. This may lead to an underuse of anticoagulant therapy. Direct oral anticoagulants (DOACs) are at least as effective as conventional therapy, but with lesser risk of intracranial hemorrhage. The simplification of treatment with these drugs may be an advantage in patients with cognitive impairment. The great majority of elderly patients with AF should receive anticoagulant therapy, unless an unequivocal contraindication. DOACs may be the drugs of choice in many elderly patients with AF. Summary In this manuscript, the available evidence about the management of anticoagulation in elderly patients with AF is reviewed. In addition, specific practical recommendations about different controversial issues (i.e. patients with anemia, thrombocytopenia, risk of gastrointestinal bleeding, renal dysfunction, cognitive impairment, risk of falls, polymedication, frailty, etc.) are provided.